2019
DOI: 10.3897/neotropical.14.e34839
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-tree use and frequency of response to playback by the Tropical Screech-Owl in northwestern Argentina

Abstract: The Tropical Screech-Owl (Megascops choliba) is a nocturnal raptor with a wide distribution across the Neotropics, which uses cavity trees as nesting and roosting sites. Our objectives were to address cavity use by the Tropical Screech-Owl in the piedmont forest of Argentina and to evaluate if logging affects the availability of suitable cavities for nesting and roosting and the frequency of response of the species to playback. The Tropical Screech-Owl used trees with DBH values > 46 cm of three tree specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Given that tree characteristics such as species, decay stage affect nest site selection and nestling survival for a broad range of cavity-nesting birds (e.g. Mahon and Martin 2006, Schaaf et al 2019), forest management which aims to balance timber harvesting with the persistence of cavity-nesting populations should focus on appropriate tree selection. While market demand for indigenous timber has declined (no trees have been harvested in the region since 2017), sustainable resource use remains a central management goal for these forests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that tree characteristics such as species, decay stage affect nest site selection and nestling survival for a broad range of cavity-nesting birds (e.g. Mahon and Martin 2006, Schaaf et al 2019), forest management which aims to balance timber harvesting with the persistence of cavity-nesting populations should focus on appropriate tree selection. While market demand for indigenous timber has declined (no trees have been harvested in the region since 2017), sustainable resource use remains a central management goal for these forests.…”
Section: Discussionmentioning
confidence: 99%
“…data), to be an artefact of selective harvesting practices, supported by the relatively high abundance of these stems recorded in mistbelt forests in KwaZulu-Natal, where harvesting has not occurred for the past 80 years (Downs and Symes 2004). Harvest-mediated modifications to the population structure of dead and decaying trees represents a disruption to the decay process, which stands to negatively affect the availability of suitable cavities (Cockle et al 2010, Politi et al 2010, Schaaf et al 2019). For example, Paillet et al (2017) found that the decay process following tree death was the main mechanism in tree microhabitat production.…”
Section: Discussionmentioning
confidence: 99%
“…size, cavity depth, tree species) 14 , 21 . For example, large secondary cavity-nesting bird species (such as ducks, parrots and toucans) depend on trees with an appropriate entrance size and depth for nesting, which can be scarce or absent in logged forests 14 , 22 , 23 . For woodpeckers, habitat alteration can lead to difficulties in the use of substrates suitable for excavation 24 – 26 and it can reduce the abundance of these birds 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%